Continuous exposure of three successive generations of mice to electromagnetic fields: implication on double minute frequency (Faculty of Medicine Universitas Indonesia, 2011)
Background: Epidemiological studies indicate increased risk of leukemia, lymphoma, and brain tumor among electrical workers exposed to electromagnetic field (EMF). Other investigator reported that continuous exposure of four successive generations of mice to EMF in doses of 1 kV to 5 kV caused tumor formation in offspring. The objective of this study was to evaluate the effect of continuous exposure of three successive generations of mice (Mus musculus L) to EMF of 3 kV, 4 kV, and 5 kV and its implication of chromosomal breakage, as detected by double minute formation.Methods: Four couples of mice of Swiss Webster strain, 3-4 months of age, and 7-40 gram of body weight were exposed to EMF at the doses of 3 kV, 4 kV, and 5 kV, and one couple served as control. Double minute formation was examined in all offspring, except one couple of each group to be exposed with the same doses of EMF to get the F2 generation, and so forth until F3 generation. Twenty metaphases of chromosomes were examined and frequencies of double minute were calculated in the three generations of all group.Results: Frequencies of double minute in F1, F2, and F3 of mice exposed to EMF of 3 kV were respectively 0.78 ± 0.08; 0.83 ± 0.09; and 0.80 ± 0.05. In the 4 kV group were 0.083 ± 0.11; 0.73 ± 0.03; and 0.96 ± 0.15, and in the 5 kV group were 0.96 ± 0.25; 0.75 ± 0.05; and 0.99 ± 0.33, whereas no double minute chromosomes were noted in control group. Frequencies of the double minute in mice exposed to EMF were significantly higher than control group.Conclusions: Continuous exposure of mice during three successive generations to EMF at doses of 3 kV, 4 kV, and 5 kV causes increased chromosomal breakage as detected as double minute chromosome formation. (Med J Indones 2011; 20:109-13)Keywords: chromosomal breakage, double minute, electromagnetic field, mice